Navigating Challenges in Engineering Education: A Comprehensive Examination of Kerala’s Landscape and Policy Interventions - Mahendra, K S; Kinslin, D.; Janardhanan, K A; Deekshith, D. (Indian Journal of Information Sources and Services, 2025)
This study explores the crucial link between engineering education and industry collaboration in Kerala, focusing on the disparity in industry-institute interactions across the North, Central, and South regions and their impact on employability and educational quality, especially in mechanical and electrical engineering fields. Industry-institute interaction is vital for the practical application of engineering education. Despite high-quality educational institutions, many students struggle to secure desirable jobs or salaries due to limited industrial establishments and high competition for placements. Kerala Technological University (KTU) aims to bridge this gap by connecting engineering colleges with industries through various programs. The research divides Kerala into regions and classifies educational institutions as urban or rural, using a comprehensive questionnaire to capture insights from students, teachers, placement officers, and industry recruiters. The study identifies the challenges faced by institutions with weak industry connections and suggests measures to enhance these interactions. Findings indicate that industry-institute interaction significantly enhances the quality of engineering education, highlighting the need for better alignment between academic curricula and industry needs, modernization of teaching methods, and improved infrastructure. The research underscores the importance of strengthening industry-institute interactions to improve employability and educational standards in Kerala. Successful examples of such collaborations highlight the potential benefits, calling for a concerted effort from educational institutions, industries, and the government to bridge existing gaps. Enhanced industry collaboration is essential for the future sustainability and competitiveness of engineering education in Kerala.